Optimalisasi Kontras Nukleus Sel Allium cepa melalui Afinitas Pewarnaan Methylene Blue - Putri Aulia Ramadhani; Nabila Haeranie; Natania Kusuma Putri; Ika Fatmawati Setya Ningrum; Argha Zora Purnama; Umairo Umairo; Liss Dyah Dewi Arini (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aims to analyze the structure and function of red onion (Allium cepa) epidermal cells in Cell Biology learning. The method used in this observation is microscopic on thin slices of red onion epidermal cells stained with Methylene Blue dye to increase contrast and clarify the structure of Allium cepa cells in red onions. Furthermore, this observation was carried out to identify the morphological characteristics and functions of Allium cepa cells. The results of the observation show that red onion epidermal cells have a polygonal shape with clear and regular cell walls. The visible cell structure includes transparent cytoplasm, a nucleus (cell nucleus) located in the center. In addition, stomata are seen in several epidermal cells, which function as gas exchange channels, important for the process of photosynthesis and respiration. The conclusion of this study is that understanding the structure and function of red onion (Allium cepa) epidermal cells is very relevant in Cell Biology learning, because these cells are good examples to illustrate the basic principles that apply in plant cells. This study also provides insight into the interaction between cells and the external environment, as well as the importance of the role of cells in supporting plant life.